Evaluating Electronic Record Management System (ERMS) Collective Access Using ISO 16175- 2:2011 - Indrawati, Tri; Pramudyo, Gani Nur (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
The aim of the study is to evaluate ERMS software of Collective Access using functional requirements of search and retrieval in ISO 16175-2: 2011. A qualitative approach was chosen as the method to evaluate Collective Access. Data were collected with observation and documentation. The finding shows that Collective Access only meets 18 of 26 attributes of functional requirements (199-225). 8 attributes of functional requirements not met, include: 1) Provide searching tools for free text and boolean searching (204); 2) Provide for 'wild card' searching (205); 3) Allow users to retrieve aggregations through the use of a unique identifier (2011); 4) Allow user to save and re-use queries (216); 5) allow the user to refine (narrow) searches (218); 6) Provide relevance ranking of the search results (222); 7) Provide concept searches use a thesaurus (224); 8) Provide browsing mechanism in form graphics/display (225). Collective Access needed to be developed for instances, adding feature keeping and using history queries, history search, narrow search, boolean operator, variation of the wild card, unique identifier, and thesaurus. Finally, the study is limited to certain functional requirements, standards, and applications. Future study needs to consider aspects that have not been discussed or comparisons with certain standards or applications.Â